2014
DOI: 10.1097/aln.0000000000000351
|View full text |Cite
|
Sign up to set email alerts
|

AMPAkines Have Novel Analgesic Properties in Rat Models of Persistent Neuropathic and Inflammatory Pain

Abstract: Background Novel analgesics that do not suppress the respiratory drive are urgently needed. Glutamate signaling through α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) receptors plays important roles in central pain circuits. AMPAkines augment AMPA receptor function and have been shown to stimulate the respiratory drive to oppose opioid-induced hypoventilation. However, their role in chronic pain states remains unknown. Methods We studied AMPAkines (CX546 and CX516) in rat spared nerve injury (SN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 77 publications
3
33
0
Order By: Relevance
“…26,27,32,33,54,55 We have previously shown that systemic administration of CX546 can relieve both sensory hypersensitivity and depressive behaviors in response to chronic neuropathic pain and inflammatory pain in rats. 56 The pathogenesis and maintenance of acute postoperative and chronic pain, however, are different mechanistically at synaptic and circuit levels. 57 Hence, we wanted to test whether CX546 could also relieve acute postoperative pain in the PI model.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…26,27,32,33,54,55 We have previously shown that systemic administration of CX546 can relieve both sensory hypersensitivity and depressive behaviors in response to chronic neuropathic pain and inflammatory pain in rats. 56 The pathogenesis and maintenance of acute postoperative and chronic pain, however, are different mechanistically at synaptic and circuit levels. 57 Hence, we wanted to test whether CX546 could also relieve acute postoperative pain in the PI model.…”
Section: Resultsmentioning
confidence: 99%
“…56 Thus, we used the FST to assess the effects of CX546 on the depressive symptoms associated with acute incisional pain (Fig. 1B).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations